Unraveling the triad of immunotherapy, tumor microenvironment, and skeletal muscle biomechanics in oncology - Shuang Ma; Ying Lu; Shang Sui; Jia-shuo Yang; Bing-bing Fu; Pei-xin Tan; Yicheng Chai; Jiaqi Lv; Lingyu Kong; Xiaolin Wu; Yi-bo Gao; Tao Yan (Frontiers in Immunology)
The intricate interaction between skeletal muscle biomechanics, the tumor microenvironment, and immunotherapy constitutes a pivotal research focus oncology. This work provides a comprehensive review of methodologies for evaluating skeletal muscle biomechanics, including handheld dynamometry, advanced imaging techniques, electrical impedance myography, elastography, and single-fiber experiments to assess muscle quality and performance. Furthermore, it elucidates the mechanisms, applications, and limitations of various immunotherapy modalities, including immune checkpoint inhibitors, adoptive cell therapy, cancer vaccines, and combined chemoimmunotherapy, while examining their effects on skeletal muscle function and systemic immune responses. Key findings indicate that although immunotherapy is effective in augmenting antitumor immunity, it frequently induces muscle-related adverse effects such as weakness, fatigue, or damage, primarily mediated by cytokine release and immune activation. This work underscores the significance of immune niches within the tumor microenvironment in influencing treatment outcomes and proposes strategies to optimize therapy through personalized regimens and combinatorial approaches. This review highlights the need for further research on the formation of immune niches and interactions muscle-tumor. Our work is crucial for advancing the efficacy of immunotherapy, reducing adverse effects, and ultimately improving survival rates and quality of life of patients with cancer.